Methodology of financial risk analysis of the company - A. Isaeva; O. Dzhavadova (Вестник Северо-Кавказского федерального университета)
The article discusses the concept of financial risk, methods of mathematical probability theory used to assess economic risks, some methods for determining the risk of bankruptcy of an enterprise. It is obvious that entrepreneurial activity is impossible without risks. One of the most important tasks for enterprises is to ensure the competitiveness of their activities, and for this it is necessary to reduce financial risks. Thus, at this stage of the development of the world economy, when there is a high degree of uncertainty and economic instability that complicate the adoption and implementation of entrepreneurial decisions, especially in the field of innovative development of the enterprise, the issue of reducing entrepreneurial risks becomes particularly relevant. We have analyzed the probability of bankruptcy of the Russian diversified holding company JSC «Concern Energomera» based on the methods of E. Altman and A. Y. Belikov – G. V. Davydova, which are among the most effective and accurate models for determining the risk of bankruptcy.